Impact of foreign linkages on innovation activity of manufacturing firms in CALABARZON - Francis Mark A. Quimba; Sylwyn C. Calizo (Philippine Institute for Development Studies (PIDS), 2017)
Despite several studies exploring innovation activities in the Philippines, no clear answer has been provided to the question of whether having foreign linkages can induce knowledge transfer and innovation. This study probes deeper into the role of foreign linkages to innovation activities of manufacturing firms in the CALABARZON region. Utilizing a probit estimation and an IV regression to control for endogeneity brought forth by omitted variable bias, the results show that foreign linkages can indeed positively affect a firm's likelihood to undertake product innovation that involves the development of a new product using a technology new to the firm. On the other hand, process innovation has consistently shown to be positively influenced by foreign linkages. Given these results, it can be inferred that having foreign linkages and participating in the global value chain impacts both process and product innovations positively. Thus, it is important to highlight the need to promote stronger regional and global linkages to sustain the manufacturing growth in CALABARZON. Moreover, supporting series of training that teach the 5S system through government channels like the Technical Education and Skills Development Authority and the various state universities and colleges are as important. Highlighting the role of industrial parks and recognizing the value of establishment-level data are also key points in this study.
Keywords: 330; foreign linkages; innovation; product; process; manufacturing; CALABARZON